Let $M$ be an $n\times n$ real matrix such that $M^2+M^T=I_n$. Prove that $M$ is invertible

Here is my progress:

  • Playing with determinant:

one has $\det(M^2)=\det(I_n-M^T)$ hence $\det(M)^2=\det(I_n-M)$

and $\det(M^T)=\det(I_n-M^2)$, hence $\det(M)=\det(I_n-M)\det(I_n+M)$

Combining both equalities yield $$\det(I_n-M)(\det(I_n-M)\det(I_n+M)-1)=0$$

  • Playing with the original assumption:

transposing yields $(M^T)^2+M=I_n$, and combining gives $(M^2-I_n)^2=I_n-M$

that is $M^4-2M^2+M=0$.

$M$ is therefore diagonalizable and its eigenvalues lie in the set $\{0,1,-\frac{1+\sqrt{5}}{2},\frac{1-\sqrt{5}}{2}\}$

  • Misc

Multiplying $M^2+M^T=I_n$ by $M$ in two different ways, one has $MM^T=M^TM$

  • Looking for a contradiction ?

Supposing $M$ is not invertible, there is some $X$ such that $MX=0$. This in turn implies $M^TX=X$... So what ?

  • $\begingroup$ Explore $M$ and $M^T$ are diagonalisable in the same base and $MM^TX=M^TMX=0$ if $X\in\operatorname{ker}{M}$ $\endgroup$
    – marwalix
    May 18 '15 at 5:29
  • $\begingroup$ @marwalix I couldn't make it work with your approach. $\endgroup$ May 18 '15 at 18:54
  • $\begingroup$ It is basically the same as @abel solution $\endgroup$
    – marwalix
    May 18 '15 at 20:51

suppose $Mx = 0.$ then multiplying $$M^2 + M^T = I$$ on the left by $x,$ we get $$M^T x = x. \tag 1$$ again multiply $(1)$ by $M$ on the left gives $$MM^T x = 0 \tag 2 $$ multiplying (2) by $x^T$ on the left gives $$ 0 =x^T M M^T x = (M^\top x)^T (M^T x) = |M^T x|^2 \to M^Tx = 0 \tag 3$$ together with $(1)$ impies $x = 0.$ that is $$ Mx = 0 \implies x = 0.$$ that is equivalent to $M$ being invertible.

  • 1
    $\begingroup$ When you multiply $(2)$ by $x^T$ and get $x^TMM^Tx=0$ how do you conclude that $M^Tx=0$? $\endgroup$
    – hjhjhj57
    May 18 '15 at 5:46
  • 1
    $\begingroup$ @hjhjhj57, see my edit. $\endgroup$
    – abel
    May 18 '15 at 5:49

as a footnote, just to look at the simplest cases:

in dimension 1 $m^2 + m - 1=0$ so $m=\frac12(-1 \pm \sqrt{5})$

in 2 dimensions, set $M=\begin{pmatrix} a & b \\c & d \end{pmatrix}$ so $$ M^{\mathrm{T}}=\begin{pmatrix} a & c \\b & d \end{pmatrix} $$ and $$ M^2 = \begin{pmatrix} a^2+bc & b(a+d) \\c(a+d) & d^2+bc \end{pmatrix} $$ so the matrix condition $M^2+M^{\mathrm{T}}=I$ gives the conditions: $$ a^2+bc +a =1 \\ d^2+bc +d = 1 \\ b(a+d)+c= 0 \\ c(a+d)+b=0 $$ since $a$ and $d$ are both roots of $x^2+x+(bc-1)=0$ we require $ad=bc-1$ hence $$ |M|=-1 $$ and $M$ is non-singular.

since we also have $a+d=-1$ this forces $b=c$ and we obtain a 1-parameter family of solutions: $$ a,d=\frac12 \left(-1\pm\sqrt{5-4b^2} \right) $$


We can find explicitly the real matrices $M$ that satisfies $M^2+M^*=I$. According to the DODOM's post, $M$ is a normal matrix, and consequently, is diagonalizable over $\mathbb{C}$ by a unitary change of basis. Then $M=Pdiag((m_i)_i)P^{-1}$ where, for every $i$, $m_i^2+\overline{m_i}=1$. Since $M$ is real, there is a unitary $P$ s.t. $M=Pdiag(\lambda_1,\cdots,\lambda_k,p_1+iq_1,p_1-iq_1,\cdots,p_r+iqr,p_r-iq_r)P^{-1}$ where $n=k+2r$ and the $(\lambda_j,p_s,q_s\not=0)$ are real; morover $\lambda_j^2+\lambda_j=1$ (that implies $\lambda_j=(-1\pm\sqrt{5})/2)$ and $p_s^2-q_s^2+p_s+i(2p_sq_s-q_s)=1$ (that implies $p_s=1/2,q_s^2=-1/4$, that has no solutions).

Finally, there is an orthogonal matrix $Q$ s.t. $M=Qdiag(((-1+\sqrt{5})/2)I_p,((-1-\sqrt{5})/2)I_q)Q^{-1}$ where $p+q=n$. Note that $M$ is necessarily symmetric.

  • $\begingroup$ Very nice work on the eigenvalues; endorsed!!! $\endgroup$ May 19 '15 at 0:03
  • $\begingroup$ Hi Robert., you are welcome. $\endgroup$
    – user91684
    May 19 '15 at 3:18

This problem statement

Let $M$ be an $n\times n$ real matrix such that $M^2+M^T=I_n$. Prove that $M$ is invertible

is actually a special case of a much more general assertion, which is in fact just about as easy to prove:

Let $p(x) = \sum_0^m p_i x^i \in \Bbb C[x]$ be a complex polynomial with non-vanishing constant coefficient $p_0$, and $M$ be an $n \times n$ complex matrix satisfying $ M^\dagger = p(M)$. Then $M$ is invertible.

We prove this as follows:

Suppose $M$ is not invertible. Then there is some non-zero vector $v \in \Bbb C^n$ with

$Mv = 0; \tag{1}$

it follows that

$M^\dagger v = p(M)v = \sum_0^m p_i M^iv = p_0 v; \tag{2}$

thus, taking the (hermitian) inner product of each side with $v$:

$\langle v, M^\dagger v \rangle = \langle v, p_0 v \rangle, \tag{3}$

whence, using (1),

$0 = \langle Mv, v \rangle = p_0\langle v, v \rangle \ne 0; \tag{3}$

this contradiction shows that (1) cannot bind for $v \ne 0$. Hence, $\ker M = 0$ and $M$ is invertible. QED.

If we now take $M$ real and $p(x) = 1 - x^2$ the specific problem at hand is solved.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.